Total content of phosphorus in some Finnish soils - Kaila, Armi (Agricultural and Food Science, 1963)
In the present paper the total content of phosphorus in Finnish mineral soils and organic soils is discussed on the basis of data collected in connection with the writer’s various works. The material consists of 670 samples which represent both the surface soils and the deeper layers. The variation in the total phosphorus content of all the groups of soil was large with the ranges overlapping. The mean values, only, indicated some tendency to an increase in the total phosphorus content with an increase in the finer fractions in mineral soils and in the Carex-residues in the peat soils. The effect of the application of phosphorus fertilizers is usually distinctly provable as the relatively high phosphorus content of the plough layer. The variation in the total phosphorus content within a soil profile does not show any regular trend.